An L-Moment-Based Analog for the Schmeiser-Deutsch Class of Distributions. (16th October 2012) - Headrick, Todd C.; Pant, Mohan D.
Abstract : This paper characterizes the conventional moment-based Schmeiser-Deutsch (S-D) class of distributions through the method of L -moments. The system can be used in a variety of settings such as simulation or modeling various processes. A procedure is also described for simulating S-D distributions with specified L -moments and L -correlations. The Monte Carlo results presented in this study indicate that the estimates of L -skew, L -kurtosis, and L -correlation associated with the S-D class of distributions are substantially superior to their corresponding conventional product-moment estimators in terms of relative bias—most notably when sample sizes are small.